Environmental Factors Influencing Phyllosphere Bacterial Communities in Giant Pandas’ Staple Food Bamboos - Long, Juejie; Luo, Wei; Xie, Jianmei; Yuan, Yuan; Wang, Jia; Kang, Liwen; Li, Yi; Zhang, Zejun; Hong, Mingsheng (Frontiers in Microbiology, 2021)
The giant panda has developed a series of evolutionary strategies to adapt to a bamboo diet. The abundance and diversity of the phyllosphere microbiome change dramatically depending on the season, host species, location etc., which may, in turn, affect the growth and health of host plants. However, few studies have investigated the factors that influence phyllosphere bacteria in bamboo, a staple food source of the giant panda. Amplicon sequencing of the 16S rRNA gene was used to explore the abundance and diversity of phyllosphere bacteria in three bamboo species (Arundinaria spanostachya, Yushania lineolate and Fargesia ferax) over different seasons (spring vs. autumn), elevation, distance from water, etc. in Liziping National Nature Reserve (Liziping NR), China. And whole-genome shotgun sequencing uncovered the differences in biological functions (KEGG and Carbohydrate-Active enzymes functions) of A. spanostachya phyllosphere bacteria between in spring and in autumn. The results showed that the abundance and diversity of F. ferax phyllosphere bacteria were greater than that of the other two bamboo species in both seasons. And three kinds of bamboo phyllosphere bacteria in autumn were significantly higher than in spring. Season was an more important factor than host bamboo species in determining the community structure of phyllosphere bacteria based on the (un)weighted UniFrac distance matrix. The composition, diversity and community structure of phyllosphere bacteria in bamboo were primarily affected by the season, species, altitude, tree layer and shrub layer. Different bacterial community perform different functions between different bamboo species, and long-term low temperatures may shape more varied and complex KEGG and Carbohydrate-Active enzymes functions in spring. Our study presented a deeper understanding of factors influencing the bacterial community in the bamboo phyllosphere. These integrated results offer an original and first insight in the bamboo, which can provide a reference for the restoration and management of giant panda bamboo food resources in Xiaoxiangling mountains.